New country data of some mayflies (Ephemeroptera) from Europe - Kovács, Tibor; Murányi, Dávid (Magyar Természettudományi Múzeum Mátra Múzeuma, 2013)
Twelve species: Siphlonurus lacustris Eaton, 1870, Baetis alpinus (Pictet, 1843), B. digitatus Bengtsson, 1912, B. kozufensis Ikonomov, 1962, B. liebenauae Keffermüller, 1974, B. lutheri Müller- Liebenau, 1967, B. melanonyx (Pictet, 1843), B. muticus (Linnaeus, 1758), Centroptilum luteolum (Müller, 1776), Habrophlebia lauta Eaton, 1884, Ephemera lineata Eaton, 1870, and Caenis strugaensis Ikonomov, 1961 are new to the fauna of Albania. Five species: Baetis liebenauae, B. lutheri, Cloeon simile Eaton, 1870, Serratella ikonomovi Puthz, 1971 and Caenis strugaensis are new to the fauna of Montenegro. Ecdyonurus insignis (Eaton, 1870), and Brachycercus harrisellus Curtis, 1834 are new to the Croatian, while Serratella albai (González del Tánago & García de Jalón, 1983) to the Portuguese, and Baetis beskidensis Sowa, 1972 to the Romanian fauna. In addition, occurrence of Serratella ikonomovi is confirmed for Albania.